Kedudukan dan Peran Filsafat dalam Pembelajaran Matematika - Alianus Zalukhu; Herman Herman; Doni Berkat Tabah Hulu; Nesti Surya Astuti Zebua; Tutiarni Naibaho; Ruthmayasari Simanjuntak (Journal on Education, 2023)
In essence, the position of science is to facilitate human life. Likewise with mathematics which is classified as a science. The birth of mathematics is none other than to provide convenience and overcome various life problems. Philosophy is a science that seeks the truth value of the essence of a problem. Philosophy and mathematics have no doubt that from the past until now these two fields of knowledge are very closely related. Philosophy of mathematics is a branch of philosophy that examines the philosophical assumptions, foundations and effects of mathematics. The aim of the philosophy of mathematics is to provide a record of the nature and methodology of mathematics and to understand the place of mathematics in human life. The position and relevance of philosophy in learning mathematics can be seen in epistemology, mathematical ontology, mathematical methodology, and mathematical logic.